Biochemical Composition and Consumption Risk of Leafy Vegetables Puts and Babenda Cereals Produced in Five Cities in Burkina Faso - Bakary, Tarnagda; Oumarou, Zongo; Korotimi, Traore; Fulbert, Nikiema; Pane, Sourabie Bernadette; Maxime, Drabo Koine; Yves, Traore; Aly, Savadogo (Journal of Food Technology Research, 2020)
Babenda is a national dish that has become famous in food habits and production without adequate knowledge of its nutritional and energy potential. It is made with leafy vegetables and cereals. This study aimed to determine the risk assessement of some heavy metals and physico-chemical characteristics of leafy vegetables and Babenda consumed in five cities in Burkina. The samples of 120 leafy vegetables and 60 Babenda were collected. The analyzes focused on the total levels of lead (Pb), cadmium (Cd), arsenic (As) and mercury (Hg) and were carried out using standard methods. The moisture content varied between 86.82 ± 2.51 and 88.57 ± 1.19. The lipid content varied from 13.89 ± 0.22g/100g to 19.91 ± 0.41g/100g, the carbohydrate content ranged from 60.91 ± 0.2 g/100g to 77.35 ± 0.22 g/100g; the protein content between 9.76 ± 0.09g / 100g and 23.56 ± 0.02g / 100g. The energy potential was between 469.45 kcal and 499.57kcal with an average value of 480.766 Kcal 100g of dry matter. Babenda is a source of calcium (129.52 ± 2.38mg / 100g), sodium (12.92 ± 0.29mg / 100g). Babenda has a good nutritional value and its consumption can help fight against food insecurity and malnutrition.